Implementasi Full Day School di SMA Negeri 1 Palipi Desa Saor Nauli Kecamatan Palipi - Isabella Yosandira Sitanggang; Ayu Rulyani (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The implementation of full day school in each school can face different dynamics according to the conditions and characteristics of the environment where the policy is implemented. These conditions are the basis for studying the implementation of full day school in SMA Negeri 1 Palipi, Saor Nauli Village. The study aims to examine the implementation of full day school and analyze the obstacles that influence its implementation in SMA Negeri 1 Palipi, Saor Nauli Village. The type of research used is qualitative with a descriptive approach. Data collection techniques are observation, interviews and documentation. Implementation began at the beginning of the odd semester, precisely on July 16, 2025. Activities were carried out with an allocation of 10 hours of lessons every day, starting from 07.00–16.00 WIB with 2 breaks, namely at 10.15–10.30 and 12.45–13.45 WIB. Obstacles also influence its implementation, including: (1) the inconsistency of the longer duration in the full day school system with the characteristics of the community, the majority of whom are farmers; (2) limited access to transportation caused by the diverse conditions of the organization, such as the location of the organization which is separated in the waters of Lake Toba and the organization which is in the highland area; (3) inadequate facilities and infrastructure to support the needs of the full day school system activity process; (4) the learning process which is not conducive due to inadequate support from the school's readiness; and (5) the physical and psychological condition of students and teachers. Thus, the implementation of full day school at SMA Negeri 1 Palipi still requires various adjustment efforts and support so that its implementation can run more optimally in accordance with the internal and external conditions of the school.